Socio-economic impacts of clean energy transition in Bangladesh - Nahid, Firuz Ahamed; Akter, Khadiza; Motakabber, S. M. A.; Alam, A. H. M. Zahirul (IEEE, 2025)
This study utilizes the PyPSA framework to evaluate the capacity expansion and socio-economic implications of Bangladesh's shift to a clean energy system, addressing its heavy reliance on fossil fuels (69% of electricity from gas and coal). Three scenarios are modeled: 30% renewable energy by 2030, 50% by 2040, and 100% clean energy by 2050. Leveraging high-resolution national official data, the analysis quantifies capacity expansion, employment, land requirements, and investment. The 2030 scenario projects 65.58 GW capacity (23.57 GW solar), generating 59.63 TWh renewables, 885,440 jobs, and requiring €77.03 billion. By 2040, an optimal capacity of 137.19 GW (69.28 GW solar) delivers 156.92 TWh, creating 2,824,362 jobs with €136.56 billion investment. The 2050 scenario achieves 474.9 TWh from 298.7 GW (176.58 GW solar, 62.81 GW wind) installation, yielding 7,074,651 jobs and needing €254.43 billion. This transition eliminates fossil fuel dependence, enhances energy affordability, and promotes equitable economic growth. Land use escalates to 3,300.41 sq.km (2.23% of Bangladesh's total land) by 2050, posing challenges in a land-constrained nation. Strategic policies promoting solar and wind incentives, innovative land-use solutions like rooftop and floating solar, and green financing mechanisms are essential to ensure the clean energy transition, ensure energy affordability, and drive inclusive economic growth, positioning Bangladesh as a leader in sustainable development.